Diagnosis and Management of Frailty in Primary Health Care - Won, Chang Won (Korean J Fam Med, 2020)
Disability in older adults has become a significant burden, both individually and socially, due to the rapidly aging population in Korea. It is important to manage both frailty and chronic diseases to delay disability. Frailty, which is considered to be a transition phase between healthy status and disability, is defined as a significant decline in functional reserves of multiple organ systems and the resultant extreme vulnerability to stressors, leading to a higher risk of adverse health-related outcomes. The frailty phenotype and frailty index are the most commonly used methods to diagnose frailty. Frailty is related to physical, psychological, cognitive, and social dysfunction, and is sometimes caused by chronic disease. Therefore, primary care providers are ideally situated to incorporate the concept of frailty into their practice, as they are champions in comprehensive care. Although the identification and treatment of frailty is not yet standard practice in primary care, primary care physicians must use the electronic frailty index to identify frailty in all the patients aged ≥65 years in the United Kingdom. In Canada, some insurance companies and governments are using a similar program, which is called the Community Actions and Resources Empowering Seniors model. The clinical practice guidelines of the International Conference of Frailty and Sarcopenia Research, as well as some additional references, will be introduced. Here, we review the current literature on how to diagnose and manage frailty in primary care.